Improved design of hydroelectric projects : hydraulic roughness of TBM-bored tunnels. An experimental study. - Filipek, Katarzyna; Kasprzyk, Anna (2011)
Verkefnið er unnið í tengslum við Háskóla Íslands og Háskólann á Akureyri The purpose of this thesis is to link head loss coefficients in rough pipes to the physical roughness of the surface through measurements of head loss in fully turbulent flow. It is generally regarded that hydraulic roughness is some function of the height, spacing, density and nature of the physical roughness under consideration. Attempts have been made to link hydraulic roughness to physical roughness of an irregular surface. Those have, however, been incomplete and conducted at flow states which do not allow concrete conclusions to be drawn. Further research on the topic is therefore needed to define a fully mature assessment methodology. The interior of the pipe were scanned and different methods to convert physical roughness to hydraulic roughness were tested. Two different types of profiles were identified and different methods suggested for each type. The thesis shows connection between the experimental results with measured head loss in hydroelectric projects in operation and deduces hydraulic friction values for different rock types in tunnels excavated with tunnel boring machines. Hydraulic head loss coefficients for different rock types were finally suggested based on the accuracy of the method tested in the pipe flow experiments. Tunnel boring machine (TBM) technology has not been used for the construction of water tunnels in Poland. However, the methodology implemented for this thesis project offers more accurate head loss estimation, crucial for future investments in Polish HEPs.